3, 6-Di(pyridin-2-yl)-1, 2, 4, 5-tetrazine capped Pd(0) nanoparticles: a catalyst for copper-free Sonogashira coupling of aryl halides in aqueous medium1. Issue 92 (8th October 2015) - Das, Sudipto; Samanta, Suvendu; Ray, Shounak; Biswas, Papu
<x xml:space="preserve">Abstract</x> 3, 6-Di(pyridin-2-yl)-1, 2, 4, 5-tetrazine (pytz) capped Pd(0) nanoparticles (TzPdNPs) act as a catalyst in Sonogashira coupling under copper- and ligand-free conditions in aqueous medium.